Two-level network design with intermediate facilities: An application to electrical distribution systems - Costa, Alysson M.; França, Paulo M. [UNESP]; Lyra Filho, Christiano (Elsevier, 2011)
We consider the two-level network design problem with intermediate facilities. This problem consists of designing a minimum cost network respecting some requirements, usually described in terms of the network topology or in terms of a desired flow of commodities between source and destination vertices. Each selected link must receive one of two types of edge facilities and the connection of different edge facilities requires a costly and capacitated vertex facility. We propose a hybrid decomposition approach which heuristically obtains tentative solutions for the vertex facilities number and location and use these solutions to limit the computational burden of a branch-and-cut algorithm. We test our method on instances of the power system secondary distribution network design problem. The results show that the method is efficient both in terms of solution quality and computational times. © 2010 Elsevier Ltd.
Keywords: Electrical distribution networks; Facility location; Heuristics; Two-level networks